The Mexican border region after NAFTA: Attempting to surpass the assembly industry - Alfredo Hualde (European Regional Science Association (ERSA), 1998)
In the last twenty years their has been an astonishing degree of industriali- zation on the Mexican border, in large part due to the arrival of foreign plants attracted by lower labor costs. This in keeping with the conception of the maquiladora program as a way to attract labor-intensive production to Mexico in order to provide more jobs and their benefits to the Mexican economy. At the end of the century a more balanced judgment has emerged. Foreign plants have invested in more intensive production processes, and more sophisticated organizational procedures: Advanced product manufacturing, just-in-time methods, and ISO9000 certification have become standard among a growing number of maquiladoras. As a consequence, knowledge of local engineers in industrial processes has remarkably increased in the last two decades. In our work we analyze those contradictory trends that make of the border region one of the most dynamic in the world. From the perspective of regional development it is necessary to asses if the industry will evolve into a more integrated network with old and new local industries, and if professional knowledge will be a more significant competitive advantage than low wages in the next few years. As Gereffi has stressed, there are different production roles among different countries;ranging from primary commodity exports to original brand-name manufacturing. Adopting the global commodity approach, we will assess whether the Mexican border region will be able to develop the ability to proceed to more sophisticated high-value industrial niches. ial niches.
Keywords: 330